The lavender garden eaudiobook - Riley, Lucinda (Recorded Books Inc., 2013)
La COte d' Azur, 1998: In the sun-dappled south of France, Emilie de la MartiniEres, the last of her gilded line, inherits her childhood home, a magnificent chAteau and vineyard. With the property comes a mountain of debt— and almost as many questions . . . Paris, 1944: A bright, young British office clerk, Constance Carruthers, is sent undercover to Paris to be part of Churchill' s Special Operations Executive during the climax of the Nazi occupation. Separated from her contacts in the Resistance, she soon stumbles into the heart of a prominent family who regularly entertain elite members of the German military even as they plot to liberate France. But in a city rife with collaborators and rebels, Constance' s most difficult decision may be determining whom to trust with her heart. As Emilie discovers what really happened to her family during the war and finds a connection to Constance much closer than she suspects, the chAteau itself may provide the clues that unlock the mysteries of her past, present, and future. Here is a dazzling novel of intrigue and passion from one of the world' s most beloved storytellers.